Settled - David Mann (The Thinker)
Settled is a work of short fiction concerned with the notions of value and extraction in the arts, and the unequal relationships of power this imposes. It was written as part of a collection of short stories that seeks, through the lens of fiction, to provide an alternative record and critique of the South African art world. The collection was produced over the course of a Creative Writing Masters programme at the University of Witwatersrand, under the supervision of Ivan Vladislavic. The idea of the ‘borrow pit’ in the story is made in reference to South African theatre-maker Jemma Kahn’s 2018 play The Borrow Pit.